2019
DOI: 10.1371/journal.pone.0220159
|View full text |Cite|
|
Sign up to set email alerts
|

Second-line HIV treatment failure in sub-Saharan Africa: A systematic review and meta-analysis

Abstract: Background Increased second-line antiretroviral therapy (ART) failure rate narrows future options for HIV/AIDS treatment. It has critical implications in resource-limited settings; including sub-Saharan Africa (SSA) where the burden of HIV-infection is immense. Hence, pooled estimate for second-line HIV treatment failure is relevant to suggest valid recommendations that optimize ART outcomes in SSA. Methods We retrieved literature systematically from PUBMED/MEDLINE, EMB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 93 publications
4
64
0
Order By: Relevance
“…The overall incidence of second-line treatment failure in this study was similar with studies conducted in African and Asian countries [18][19][20]. However, the incidence of the treatment failure of this study was lower as compared to the study conducted in South Africa, other studies from African and Asian patients, Amhara region, Ethiopia (9.86 per 100 PYs) and systematic analysis (15.0 per 100 PYs) [17,[21][22][23]. The cumulative incidence of this study is however higher compared to the study conducted in the north western Ethiopia (61.7/1000 PYs) [16].…”
Section: Plos Onesupporting
confidence: 82%
“…The overall incidence of second-line treatment failure in this study was similar with studies conducted in African and Asian countries [18][19][20]. However, the incidence of the treatment failure of this study was lower as compared to the study conducted in South Africa, other studies from African and Asian patients, Amhara region, Ethiopia (9.86 per 100 PYs) and systematic analysis (15.0 per 100 PYs) [17,[21][22][23]. The cumulative incidence of this study is however higher compared to the study conducted in the north western Ethiopia (61.7/1000 PYs) [16].…”
Section: Plos Onesupporting
confidence: 82%
“…Although DRMs were common after first-line ART failure, switching to second-line bPI-based ART demonstrated suppression to <1,000 copies/mL in 53/60 (88%), consistent with studies among HIV-infected children and adults where VS in response to second-line regimens range from 70% to 95% after 48 weeks of follow-up. [33][34][35][36][37][38][39] We observed that overall, first-line ART failures who changed to a new NRTI were more likely to achieve VS on secondline regimens compared to those who continued on the same NRTI ( p = .031) (Fisher's exact test). Genotyping before the switch to second-line regimens demonstrated M184V (72%) and K65R (41%) at first-line ART failure.…”
Section: Discussionmentioning
confidence: 99%
“…High rates of VS similar to those reported in other studies provide reassurance of effective VS on a PI-based second-line ART. [35][36][37] However, when the NRTI backbone is not optimized after failure of firstline ART, concern is raised about the durability of second-line treatment, particularly with ATV/r as the sole active agent in a population where many decades of continued treatment are anticipated. The costs, long-term adherence to bPIs, together with the increasing prevalence of NNRTI DRMs support the recent recommendations to adopt Integrase Strand Transfer Inhibitors such as dolutegravir (DTG).…”
Section: Discussionmentioning
confidence: 99%
“…If inadequately treated, children progress much faster to AIDS and death [8][9][10]. As children's initial ART regimens are often their best opportunity for effective, tolerable treatment, optimizing the time on a successful initial regimen may result in greater long-term effectiveness of ART and more lifetime treatment options [11]. Analyzing longitudinal relationships between pediatric ART regimens and time to treatment disruption allows identification of initial ART regimens that pose greater challenges to maintaining optimal, continuous ART.…”
Section: Introductionmentioning
confidence: 99%